Concentration et convergence des médias en Amérique latine - Martín Becerra; Guillermo Mastrini (Communiquer)
The article analyzes media concentration process and convergent activities such as telecommunications and the Internet in Latin America, as this process is one of the main reasons for the adoption, by the governments of the region, of new regulations for a decade. Analyzing the concentration of the activities of production, storage, distribution and exhibition of information and communication, this article characterizes the main conglomerates working in the region, compares their economic scope and their main sectors of intervention. Indicators of the concentration process that contribute to its quantification are also presented.